Analisis Kelengkapan Desain Formulir Pasien Rawat Jalan Di Puskesmas Purwokerto Timur I - Cahyani, Lintang Dwi; Hakim, Agya Osadawedya; Indira, Zahrasita Nur; Permatasari, Merdiana Ika (Akademi Perekam dan Informasi Kesehatan Imelda, 2024)
Puskesmas is one of the health service institutions provided by the Indonesian government and is the spearhead of the national health system. Efforts in establishing quality health centre service quality, that is, by paying attention to every aspect of it. The anatomical and physical aspects are used here. Please note the number of measurement cards for patients. One of them is processing the patient's medical record form design. Medical record forms are designed and used for maintenance and monitoring. The design of the form aims to improve and complete aspects of the outpatient form design that are currently still in use and to improve the quality of health services at the Purwokerto Timur I Health Center. The objective of this research is to identify the completeness of the outpatient forms available at the Purwokerto Health Center. Timur I. This analysis uses a quantitative method with a cross-sectional descriptive approach. The subject of this study was the outpatient form at the Purwokerto Timur I Health Center. The results obtained from this study were quite good, that is, there was an outpatient form at the Purwokerto Timur I Health Center, but the results of the analysis of this form still need to be improved in completeness. There is a completeness of 76,92% in the form. The aspect of the content that has the best completeness of the form.